Women, work, and economic growth : leveling the playing field - Kochhar, Kalpana; Newiak, Monique; Jain-Chandra, Sonali (Washington, D.C International Monetary Fund (IMF), 2017)
Women make up a little over half of the world’s population, but their contribution to measured economic activity and growth is far below its potential. Despite significant progress in recent decades, labor markets across the world remain divided along gender lines, and progress toward gender equality seems to have stalled. The challenges of growth, job creation, and inclusion are closely intertwined. This volume brings together key research by IMF economists on issues related to gender and macroeconomics. In addition to providing policy prescriptions and case studies from IMF member countries, the chapters also look at the gender gap from an economic point of view. (IMF)
​Foreword by Christine Lagarde -- Acknowledgments -- PART I OVERVIEW 1 Introduction / Kalpana Kochhar, Sonali Jain-Chandra, and Monique Newiak -- 2 Gender Inequality around the World / Sonali Jain-Chandra, Kalpana Kochhar, Monique Newiak, Tlek Zeinullayev, and Lusha Zhang -- PART II THE MACROECONOMIC GAINS FROM GENDER EQUITY 3 Gender Inequality and Macroeconomic Performance / David Cuberes, Monique Newiak, and Marc Teignier -- 4 Tackling Income Inequality / Christian Gonzales, Sonali Jain-Chandra, Kalpana Kochhar, Monique Newiak, and Tlek Zeinullayev -- 5 Empowering Women Can Diversify the Economy / Romina Kazandjian, Lisa Kolovich, Kalpana Kochhar, and Monique Newiak -- PART III TACKLING GENDER INEQUALITY AROUND THE GLOBE 6 Tackling Gender Inequality in Asia -- 7 Tackling Gender Inequality in Europe -- 8 Tackling Gender Inequality in the Middle East -- 9 Tackling Gender Inequality in Sub-Saharan Africa - 10 Tackling Gender Inequality in the Western Hemisphere -- PART IV POLICIES TO LEVEL THE PLAYING FIELD 11 Tax and Spending Policies to Achieve Greater Gender Equality / Benedict Clements and Janet G. Stotsky -- 12 Equal Laws and Female Labor Force Participation / Christian Gonzales, Sonali Jain-Chandra, Kalpana Kochhar, and Monique Newiak -- Author Biographies Index
Includes bibliographies
Keywords: Labour force; EQUALITY; ECONOMIC GROWTH; WOMEN WORKERS; FEMALE LABOUR; Gender Equality